Assessment of anxiety levels in patients during elective upper gastrointestinal endoscopy and colonoscopy - Feyzullah ERSÖZ; Ahmet Burak TOROS; Gülşen AYDOĞAN; Hasan BEKTAŞ; Özhan ÖZCAN; Soykan ARIKAN (Turkish Journal of Gastroenterology, 2019)
-